A novel dual-parameter method for evaluating seismic collapse severity in masonry pagodas - Mingdong Li; Junlong Lu; Defa Wang; Xin Jia; Xiaoqin Wu; Dongxu Mao; Zuoyi Yun; Zhenshan Wang (Bulletin of Earthquake Engineering, 2026)

Triterpenoid saponins from Caragana korshinskii Kom.: α ‑glucosidase inhibitory activity and characterisation of four new compounds - Yumei Ma; Tao Chen; Zhibo Song; Hailun Feng; Defa Kong; Juyuan Luo; Shuo Wang; Cheng Shen; Yulin Li (Natural Product Research, 2026)

Single-electrode multiplex sensing via metal ion displacement method - Yiming Zhang; Zhi Chen; Songrui Wei; Huiling Lin; Yujun Zhang; Yingxia Liu; Jing Wang; Qi Gao; Defa Li; Han Zhang; Zhongjian Xie (Chemical Engineering Journal, 2025)

Unraveling the catalytic pyrolysis of oleic acid to produce biodiesel-range hydrocarbon fuel with Ni-loaded Ce-Zr mesoporous catalysts by tuning the crystal face structure - Meihua Fu; Huaiyuan Tang; Jida Wang; Defa Hou; Fulin Yang; Yi Lu; Can Liu; Xu Lin; Zhifeng Zheng; Yunwu Zheng (Fuel, 2025)

Engineered synthesis of Fe-Mn bimetallic anchored hierarchical bamboo-derived activated carbon: Dual-functional platform for ultrahigh-capacity phenol adsorption and high-energy supercapacitors - Tao Pei; Kang Yang; Hongyuan Wang; Xuewen Yang; Yuwen Xue; Defa Hou; Fulin Yang; Yi Lu; Can Liu; Xu Lin; Hao Sun; Hui Gao; et al. (Chemical Engineering Journal, 2025)

Hydrothermal co-carbonization of medium-density fiberboard with N-rich compounds to produce N-containing compounds and N-doped biochar: Product distribution, nitrogen transformation pathway and electrochemical performance - Hongyuan Wang; Yuwen Xue; Defa Hou; Yi Lu; Fulin Yang; Can Liu; Xu Lin; Chengguo Liu; Zhifeng Zheng; Yunwu Zheng (Fuel, 2025)

In-depth understanding of the synergistic effect in catalytic copyrolysis of lignin-plastic mixtures with lignin-tailored hierarchical HZSM‑5 catalysts - Yifei Chen; Meihua Fu; Jida Wang; Defa Hou; Yi Lu; Fulin Yang; Can Liu; Xu Lin; Zhifeng Zheng; Yunwu Zheng (Fuel, 2024)

Green diesel-like hydrocarbon production by H2-free catalytic deoxygenation of oleic acid via Ni/MgO-Al2O3 catalysts: Effect of the metal loading amount - Feng Shi; Hongyuan Wang; Yifei Chen; Yanling Lu; Defa Hou; Can Liu; Yi Lu; Xu Lin; Xiaoqin Yang; Zhifeng Zheng; Yunwu Zheng (Journal of Environmental Chemical Engineering, 2023)

Highly stable Mo-based bimetallic catalysts for selective deoxygenation of oleic acid to fuel-like hydrocarbons - Jida Wang; Yifei Chen; Can Liu; Yi Lu; Xu Lin; Defa Hou; Cuiping Luo; Dechao Wang; Zhifeng Zheng; Yunwu Zheng (Journal of Environmental Chemical Engineering, 2023)

Comparison of the Variability of Small Extracellular Vesicles Derived from Human Liver Cancer Tissues and Cultured from the Tissue Explants Based on a Simple Enrichment Method - Jie Chen; Zhigang Jiao; Jianwen Mo; Defa Huang; Zhengzhe Li; Wenjuan Zhang; Tong Yang; Minghong Zhao; Fangfang Xie; Die Hu; Xiaoxing Wang; Xiaomei Yi; et al. (Stem Cell Reviews and Reports, 2022)
A potential use of small extracellular vesicles (sEVs) for diagnostic and therapeutic purposes has recently generated a great interest. sEVs, when purified directly from various tissues with proper procedures, can reflect the physiological and pathological state of the organism. However, the quality of sEV is affected by many factors during isolation, including separation of sEV from cell and tissues debris, the use of enzymes for tissue digestion, and the storage state of tissues. In the present study, we established an assay for the isolation and purification of liver cancer tissues-derived sEVs (tdsEVs) and cultured explants-derived sEVs (cedsEVs) by comparing the quality of sEVs derived from different concentration of digestion enzyme and incubation time. The nano-flow cytometry (NanoFCM) showed that the isolated tdsEVs by our method are purer than those obtained from differential ultracentrifugation. Our study thus establishes a simple and effective approach for isolation of high-quality sEVs that can be used for analysis of their constituents. Graphical abstract

Metabolic characteristics and nutrient utilization in high-feed-efficiency pigs selected using different feed conversion ratio models - Beibei He; Tiantian Li; Wei Wang; Hang Gao; Yu Bai; Shuai Zhang; Jianjun Zang; Defa Li; Junjun Wang (Science China Life Sciences, 2019)

Effects of CTR4 deletion on virulence and stress response in Cryptococcus neoformans - Ping Zhang; Defa Zhang; Xueru Zhao; Dongsheng Wei; Yu Wang; Xudong Zhu (Antonie van Leeuwenhoek, 2016)